2010
DOI: 10.1007/bf03217491
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of silver nanoparticle toxicity in rat

Abstract: Silver nanoparticles (SNPs) have received considerable attention recently, because SNPs with different shapes and sizes exhibit variable antimicrobial activity, which makes them useful for medical and hygienic purposes. SNPs have been detected in various tissues and organisms after inhalation, oral ingestion, and contact with the skin, indicating that SNPs can be distributed to different body tissues after uptake. Thus, the toxicity of SNPs to different body tissues after their uptake needs to be studied. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 84 publications
(66 reference statements)
1
7
0
Order By: Relevance
“…Therefore, one hypothesis could be that in the current study a corona of intracellular proteins formed immediately around the microinjected (initially ligand-free) particles, which served to protect the embryo from detrimental nanoparticle interactions. On the other hand, the injection of silver nanoparticles into the blood stream of adult rats did result in toxic effects, even though in these trials immediate contact to proteins was given, too [7172]. It should be considered, however, that much higher dosages were applied in these tests.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, one hypothesis could be that in the current study a corona of intracellular proteins formed immediately around the microinjected (initially ligand-free) particles, which served to protect the embryo from detrimental nanoparticle interactions. On the other hand, the injection of silver nanoparticles into the blood stream of adult rats did result in toxic effects, even though in these trials immediate contact to proteins was given, too [7172]. It should be considered, however, that much higher dosages were applied in these tests.…”
Section: Discussionmentioning
confidence: 99%
“…The study was performed under non‐cytotoxic conditions and thus allows for the identification of early, adaptive cellular reactions without disturbance of data by unspecific molecular signatures of excessive cell deaths. The analysis of silver effects in the liver cells is of pivotal relevance, because animal studies have shown that a significant fraction of silver is distributed to this organ (Juling et al, ; Loeschner et al, ; Recordati et al, ; van der Zande et al, ) and that silver can exert adverse effects in this organ: reported hepatic in vivo effects of nanosilver comprise oxidative stress (Kim et al, ; Patlolla et al, ; Shrivastava, Kushwaha, Bhutia, & Flora, ), hepatocellular necrosis (Recordati et al, ), infiltration by inflammatory cells (Cha et al, ; Kim et al, ), morphological alterations (Patlolla et al, ) and an increase in proliferating cells (Garcia et al, ). Even though different rodent models and nanoparticles have been used in the aforementioned studies, the synopsis of available data reveals that by using bioinformatic analysis of biological processes associated with proteomic effects of silver in vivo, it is possible to predict in vivo effects of the metal with remarkable accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Proteomic analyses have significantly contributed to current knowledge on silver toxicity. In rat liver, oxidative stress, inflammation and apoptotic cell death have been reported following intravenous or oral application of silver (Kim et al, ; Patlolla, Hackett, & Tchounwou, ). Consequently, cellular responses to oxidative stress have also been detected by proteomic analyses in vitro (Driessen et al, ; Georgantzopoulou et al, ; Miethling‐Graff et al, ; Oberemm et al, ; Verano‐Braga et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Results showed significant alteration in expression of various genes that cause inflammatory responses and thrombosis. 97 Cerium Oxide Very recently, cerium oxide (CeO 2 ), a rare-earth oxide found in the lanthanide series of the periodic table, has been increasingly used as a nanotherapeutic material. 98 The ability of CeO 2 , also known as nanoceria, to switch between mixed oxidation states is similar to that of biological antioxidants.…”
Section: Silver Nanoparticlesmentioning
confidence: 99%